Live imaging of nuage and polar granules: evidence against a precursor-product relationship and a novel role for Oskar in stabilization of polar granule components. - Snee, M.J.; Macdonald, P.M. (Journal of Cell Science, 2004)
Nuage, a germ line specific organelle, is remarkably conserved between species, suggesting that it has an important germline cell function. Very little is known about the specific role of this organelle, but in Drosophila three nuage components have been identified, the Vasa, Tudor and Aubergine proteins. Each of these components is also present in polar granules, structures that are assembled in the oocyte and specify the formation of embryonic germ cells. We used GFP-tagged versions of Vasa and Aubergine to characterize and track nuage particles and polar granules in live preparations of ovaries and embryos. We found that perinuclear nuage is a stable structure that maintains size, seldom detaches from the nuclear envelope and exchanges protein components with the cytoplasm. Cytoplasmic nuage particles move rapidly in nurse cell cytoplasm and passage into the oocyte where their movements parallel that of the bulk cytoplasm. These particles do not appear to be anchored at the posterior or incorporated into polar granules, which argues for a model where nuage particles do not serve as the precursors of polar granules. Instead, Oskar protein nucleates the formation of polar granules from cytoplasmic pools of the components shared with nuage. Surprisingly, Oskar also appears to stabilize at least one shared component, Aubergine, and this property probably contributes to the Oskar-dependent formation of polar granules. We also find that Bruno, a translational control protein, is associated with nuage, which is consistent with a model in which nuage facilitates post transcriptional regulation by promoting the formation or reorganization of RNA-protein complexes.